SAT0019 Preliminary Data Supporting the Feasibility and Construct Validity of Promis Fatigue Instrument in an Academic Rheumatoid Arthritis Clinic. (23rd January 2014) - Bartlett, S. J.; Orbai, A.-M.; Duncan, T.; De Leon, E.; Jones, M.; Bingham, C. O.
Abstract : Background: The Patient-Reported Outcomes Measurement Information System (PROMIS) initiative of the National Institutes of Health has created item banks to measure patient-reported health outcomes for physical, mental, and social well–being across domains relevant to chronic medical conditions. PROMIS scores have a mean of 50 and standard deviation of 10, in reference to general US adult and pediatric populations. However, the feasibility of using PROMIS scales in busy settings as part of clinic visits and the validity of most PROMIS measures in persons with rheumatoid arthritis (RA) has not been demonstrated. Objectives: To contribute preliminary data on the feasibility and construct validity of the PROMIS fatigue item banks in an academic RA clinic. Methods: Consecutive RA patients enrolled in a longitudinal study completed selected patient reported outcomes (PROs) at the Johns Hopkins Arthritis Center. PROMIS fatigue items were administered using computerized adaptive test (CAT) administered on a tablet computer linked directly to the internet-based PROMIS Assessment Center immediately before a routine clinic visit. Variables were transformed as needed and descriptive statistics, correlations and multiple regression analyses were performed using IBM SPSS ver 20. Results: Participants were 69 RA patients with a mean (SD) age of 55.1 ± 13.7 yrs and RA duration of 10 ± 9 yrs, who were mostly female (77%), white (83%) and well educated (74% had some college). PROMIS fatigue t-scores ranged from 32 to 76, with a mean of 55.7 ± 10.0 and were highly correlated with fatigue VAS ratings (r=.83), moderately correlated with stiffness (r=.55), patient global (r=.66), pain VAS (r=.60), and only weakly with MHAQ (r=.39). Fatigue was moderately associated with CDAI (r=.50) though only weakly with DAS28 (r=.27), SJC (r=.24) and TJC (r=.29)(all p's <.05), but not age or sex. Patients with any level of disease activity reported fatigue levels on average 1 SD higher than those in CDAI remission (59.1 ± 8.3 vs. 49.6 ± 8.3; p<.01). In multivariate regression, after controlling for pain, fatigue was a significant predictor of Patient Global scores; together pain and fatigue explained 83% of the variance. Conclusions: Fatigue is common in RA. These results contribute preliminary evidence of the feasibility and construct validity of the PROMIS Fatigue instrument in RA with both RA PROs as well as clinician disease activity ratings. Further testing and validation of PROMIS Fatigue and other PROMIS domain instruments in RA populations is needed. Disclosure of Interest: None Declared